PSYCHIATRIC MORBIDITY AMONG PATIENTS ATTENDING CARDIAC OPD - Goyal, Ashok (Medknow Publications, 2001)
One hundred patients were selected from the cardiology outpatient department by non-probability purposive method. Each patient was evaluated by a psychiatrist and a consultant cardiologist The informations were recorded in a self designed proforma. The Hindi version of Goldberg′s General Health Questionnaire and modified adjective check list for type A and type B personality characteristics were administered. Seventy five percent of the patients were having psychiatric problems. The cardiac patients were having psychiatric problems. The cardiac patients were having predominantly type A personality characteristics. Panic disorder was the predominant diagnosis in the psychiatric patients and depression was the main diagnosis in cardiac patients. These patients presented with complaints of chest pain, palpitation, ghabarahat, weakness, increased sweating, hot and cold flushes, choking, breathlessness, decreased appetite.etc.in cardiac OPD.